2019
DOI: 10.4103/psychiatry.indianjpsychiatry_522_18
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive brain stimulation in obsessive–compulsive disorder

Abstract: Obsessive–compulsive disorder (OCD) is a complex neuropsychiatric disorder with a chronic course, contributing to significant socio-occupational dysfunction. Forty percent of patients remain treatment refractive despite mainstream treatment options such as serotonin-reuptake inhibitors and cognitive behavior therapy. Noninvasive brain stimulation approaches such as transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS) have piqued interest as add-on treatment options in OCD.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“… 5 Despite these treatment options, approximately 40% of patients did not respond to the recommended drugs or CBT. 6 Therefore, there is an urgent need to find more safe and effective treatment for OCD. Different add-on stimulation techniques could be effective for patients with severe OCD who were unresponsive to drugs and/or behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 Despite these treatment options, approximately 40% of patients did not respond to the recommended drugs or CBT. 6 Therefore, there is an urgent need to find more safe and effective treatment for OCD. Different add-on stimulation techniques could be effective for patients with severe OCD who were unresponsive to drugs and/or behavioral therapy.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the commonly used stimulation targets of OCD are dorsolateral prefrontal cortex(DLPFC),orbitofrontal cortex(OFC), and supplementary motor area(SMA). 6 The stimulation parameters used for those targets are usually low-frequency stimulation or cTBS, with suppressive effects on cortical excitability. However, studies involving DLPFC and SMA areas had reported inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas transcranial direct current stimulation (tDCS) needs more investigation for the treatment of compulsivity given the lack of sham controlled studies, repetitive Transcranial Magnetic Stimulation (rTMS) (Box 2) as non-invasive and relatively site specific, has been the most studied neuromodulation technique in the treatment of compulsive behavior in both AUD and OCD (Campbell et al, 2018; Shivakumar et al, 2019). As the time of writing, there have been 10 studies probing rTMS as a tool to change alcohol consumption and explore the associated neurocircuit changes in AUD (Table 2).…”
Section: Neuromodulatory Strategies To Target Compulsivity In Audmentioning
confidence: 99%
“…Two reviews suggest that stimulating the mPFC could enhance the effects of exposure therapy 17,18 . Moreover, noninvasive neurostimulation as a treatment augmentation strategy has demonstrated promising results in treatment-resistant contexts, such as treatment-resistant depression 19 and obsessive-compulsive disorder 20 . However, it has not been tested as a means of enhancing exposure therapy to treat extinction-resistant fears, such as biologically prepared fears, including fear in an intergroup (ie, out-group) context.…”
mentioning
confidence: 99%